2021
DOI: 10.2196/19651
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Public Reaction to Violence Against Doctors in China: Interrupted Time Series Analysis of Media Reports

Abstract: Background Violence against doctors in China is a serious problem that has attracted attention from both domestic and international media. Objective This study investigates readers’ responses to media reports on violence against doctors to identify attitudes toward perpetrators and physicians and examine if such trends are influenced by national policies. Methods We searched 17 Chinese violence against docto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that misdiagnosis, a lack of informed consent, therapeutic plan errors, procedures that result in serious complications, and patient–physician mistrust were significantly associated with medical disputes ( 9 , 31 , 32 ). These factors may be very useful in guiding medical management.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that misdiagnosis, a lack of informed consent, therapeutic plan errors, procedures that result in serious complications, and patient–physician mistrust were significantly associated with medical disputes ( 9 , 31 , 32 ). These factors may be very useful in guiding medical management.…”
Section: Discussionmentioning
confidence: 99%
“…What we think will likely happen is that scapegoating will be redirected-that is, we might see the enemyship being directed at individuals who recklessly exposed others to the virus, or to governments who failed to implement social distancing or failed to offer necessary materials, such as masks. Consistent with these observations, recent studies (Yang, Tai-Seale, et al, 2021;Yang, Wang et al, 2021;Yang, Young, et al, 2021) have found that people in China continue to show relatively aggressive intentions toward doctors in negative illness scenarios during the COVID-19 era, and in fact the threat of COVID-19 may exacerbate this tendency. There are also cultural differences in the manifestation of the scapegoating mechanism between China and the United States both before and during the pandemic: This research shows that individuals in China are more likely to blame individual caregivers, but those in the United States are more likely to blame the medical system as a whole.…”
Section: Loss Of Control and Scapegoating During The Covid-19 Pandemicmentioning
confidence: 55%
“…Nevertheless, convergent operationalizations would be informative. For instance, Yang, Tai-Seale et al (2021), Yang, Wang et al (2021), andYang, Young et al (2021) examined archival data, namely public online comments in reaction to real-world incidents of violence against doctors. In other empirical research, the correlation between aggressive behavioural intentions and aggressive behaviour was significant (r = .168, p = .013; Santos et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace violence from patients is an increasing threat to the safety and well-being of healthcare workers in China. In recent years, high rates of workplace violence against healthcare professionals have often been reported in different settings 12,13 . In cases of serious violence, there were murders and injuries, such as a doctor who had acid poured on his face and another whose throat was cut 14 .…”
Section: Introductionmentioning
confidence: 99%